Spatial and temporal frequency band changes during infarct induction, infarct progression, and spreading depolarizations in the gyrencephalic brain - Kentar, Modar; Díaz-Peregrino, Roberto; Trenado, Carlos; Sánchez-Porras, Renán; San-Juan, Daniel; Ramírez-Cuapio, F. Leonardo; Holzwarth, Niklas; Maier-Hein, Lena; Woitzik, Johannes; Santos, Edgar (Frontiers in Neuroscience, 2022)
Aim: To describe the spatial and temporal electrocorticographic (ECoG) changes after middle cerebral artery occlusion (MCAo), including those caused by spreading depolarization (SD) in the pig brain. Methods: The left middle cerebral arteries (MCAs) were clipped in six pigs. Five-contact ECoG stripes were placed bilaterally over the frontoparietal cortices corresponding to the irrigation territory of the MCA and anterior cerebral artery (ACA). ECoG recordings were performed around 24 h, and SDs were quantified. Five-minute ECoG signal segments were sampled before, 5 min, and 4, 8, and 12 h after cerebral artery occlusion and before, during, and after the negative direct current shift of the SDs. The power spectrum of the signals was decomposed into delta, theta, alpha, beta, and gamma bands. Descriptive statistics, Wilcoxon matched-pairs signed-rank tests, and Friedman tests were performed. Results: Electrodes close to the MCAo showed instant decay in all brain waves and SD onset during the first 5 h. Electrodes far from the MCAo exhibited immediate loss of fast brain waves and progressive decline of slow waves with an increased SD incidence between 6 and 14 h. After 8 h, the ACA electrode reported a secondary reduction of all brain waves except gamma and high SD incidence within 12-17 h. During the SD, all electrodes showed a decline in all brain waves. After SD passage, brain wave recovery was impaired only in MCA electrodes. Conclusions: ECoG can identify infarct progression and secondary brain injury. SDs generate severe brain frequency disturbances, regardless of the cortical location.